3D Structure, Dynamics, and Activity of Synthetic Analog of the Peptaibiotic Trichodecenin I. Issue 5 (17th May 2013) - Gatto, Emanuela; Bocchinfuso, Gianfranco; Palleschi, Antonio; Oncea, Simona; De Zotti, Marta; Formaggio, Fernando; Toniolo, Claudio; Venanzi, Mariano
Abstract In this contribution, we report on the conformational preferences of synthetic analogs of the antimicrobial peptide trichodecenin I in solution. This 6‐amino acid residue long peptide is characterized by a single, strongly helicogenic Aib residue in the central part of the sequence and is rich in the conformationally mobile Gly residues. It has been reported that, in CHCl3 solution and in the crystal state, this peptaibiotic adopts a non‐helical, multiple β‐turn conformation, whereas a 310/α‐helical structure was obtained from an X‐ray diffraction study on a trichodecenin I analog (TDT4W6) containing the fluorescent Trp residue in position 6 (replacing Ile) and an equally helicogenic TOAC residue in position 4 (replacing Aib). In this work, we applied spectroscopic techniques and molecular‐dynamics calculations, in particular, on the fluorescent TDT4W6 trichodecenin I analog with the aim at investigating its 3D‐structural and dynamical features in solution. Our results revealed that TDT4W6 can be described by an ensemble of conformers quickly interconverting in the nanosecond time scale. The most populated cluster has a conformation similar to the NMR structure of native trichodecenin I in CHCl3. However, also helical‐like conformers are present, even if poorly populated and less stable under the analytical conditions.